AR-HMD Multitask Viewing System Concept with a Supporting Handheld Viewport for Multiple Spatially-Anchored Workspaces - Oh, Seo Young; Yoon, Boram; Woo, Woontack (IEEE International Symposium on Mixed and Augmented Reality Workshops (Online), 2022)
We propose a system concept for Augmented Reality Head-Mounted Display users, which supports multitask viewing with multiple vir-tual workspaces anchored in the real-world space. Although people encounter multitasking necessities frequently, the native AR HMD and existing interfaces lack measures to visualize multiple sets of spatially-anchored information in parallel. The system separately vi-sualizes two different sets of spatially-anchored information, one on each AR HMD and smartphone, enabling side-by-side multitasking on AR HMD without applying heavy load on users. We implemented a proof-of-concept prototype that allows side-by-side viewing of the two different virtual workspaces. The proposed concept shows promises of multitasking on AR HMD, and future research will de-velop the system to be fully functional and verified with user studies.